Early hyperbaric oxygen effects on neuropathic pain and nitric oxide synthase isoforms in CCI rats - Ding, Yuanyuan (Oncotarget, 2018)
Neuropathic pain is pain caused by injury or dysfunction in the central and/or peripheral nervous system. Neuropathic pain has a high incidence with a complex mechanism, but effective treatment remains elusive. Hyperbaric oxygen (HBO) therapy has been widely used in the treatment of a variety of neurological diseases. The current study used a rat model of neuropathic pain induced by chronic constriction injury (CCI) of the sciatic nerve. We observed the effects of early use of 2.5 absolute atmosphere (ATA) HBO on neuropathic pain-related behaviors and the expression of nitric oxide synthase (NOS) isoforms in the spinal dorsal horn. In the CCI group, mechanical withdrawal threshold (MWT) was decreased, Thermal withdrawal latency (TWL) was shortened, and mRNA and protein levels of iNOS and nNOS were significantly increased compared to the sham group. MWT was increased, TWL was enhanced, and iNOS and nNOS levels were significantly decreased in the HBO group compared to the CCI group. There was no change in eNOS levels across all groups. HBO treatment at early stages can improve hyperalgesia.